Discontinuity in organisations: identifying business environments affecting efficiency of knowledge flows in Product Lifecycle Management - Ibrahim, Rahinah; Paulson, Boyd C. (Inderscience Publishers, 2008)
We conducted an ethnographic study on an affordable housing developer to understand why knowledge losses recur despite investments in Knowledge Management (KM) systems by property developers. We found four operating environmental characteristics – multiple concurrent and sequential phases, discontinuous memberships, tasks interdependencies and different dominating knowledge types for each lifecycle phases – contributing to the Knowledge-loss phenomenon. These findings suggest a review of the information processing theory in business operations since it cannot fully support the operations of highly discontinuous teams. This understanding is critical as a basis for the design and development of future KM technologies in Product Lifecycle Management (PLM). It also highlights the needs for the design and development of KM systems that cater to both the tacit- and explicit-dominant lifecycle phases within a PLM system.